Simultaneous in situ hybridisation of native mRNA and immunoglobulin detection by conventional immunofluorescence in paraffin wax embedded sections. Issue 2 (February 1992) - Harper, S J; Pringle, J H; Gillies, A; Allen, A C; Layward, L; Feehally, J; Lauder, I
Abstract : AIMS: The development of a technique for simultaneous in situ hybridisation for native mRNA and conventional immunofluorescence for cytoplasmic antigens in routine pathology specimens. METHODS: Cocktails of synthetic deoxyoligonucleotides coding for immunoglobulin J chain and kappa light chain were 3' end labelled enzymatically with digoxigenin using terminal deoxynucleotidyl transferase. Native mRNA sequences were "unmasked" using proteolytic digestion with proteinase K and hybrid detection was achieved with an alkaline phosphatase labelled anti-digoxigenin antibody. Alkaline phosphatase was visualised with Fast red/naphthol AS-MX phosphate. Fluorescein isothiocyanate (FITC) conjugated anti-isotype antibodies were used simultaneously at the detection stage to identify the isotype production by individual plasma cells in endoscopic duodenal biopsy specimens. RESULTS: The IgA plasma cells of the lamina propria were identified by immunofluorescence and hybrids were detected in the anticipated plasma cell population by Fast red visualisation. The reaction product was visible in bright field or ultraviolet illumination which allowed FITC and Fast red labels to be visualised together under ultraviolet light at 490 nm. Dual labelled cells were clearly visible. Morphology was well preserved throughout. CONCLUSIONS: This technique permits the demonstration of specific mRNA species in cells expressing immunoglobulin. It combines all the advantages of non-radioactive synthetic oligonucleotide probes and conventional immunofluorescence techniques in routine formol-saline fixed and paraffin wax embedded sections with good retention of morphology.